ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN “SCARLETT WHITENING BODYLOTION” - Ranti April Yani; Mathora Tatiana Sinambela; Irsyad Lubis (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine whether the factors studied affect customer loyalty in using Scarlett Whitening body lotion. The population used in this study were students majoring in management at the Univercity Pembangunan Panca Budi Medan with the criteria for women from the 2018-2021 class. The sample required is 81 respondents. Sampling used in this study is non-probability sampling. The type of data used in this study is primary data, namely by collecting data through questionnaires. The data analysis technique used in this research is multiple linear regression. Thus partially and simultaneously, customer satisfaction, product quality, and brand image have a significant effect on customer loyalty Scarlett Whitening bodylotion